Modulation of vestibular input by short-term head-down bed rest affects somatosensory perception: implications for space missions - Gammeri, Roberto; Salatino, Adriana; Pyasik, Maria; Cirillo, Emanuele; Zavattaro, Claudio; Serra, Hilary; Pia, Lorenzo; Roberts, Donna R.; Berti, Anna; Ricci, Raffaella (Frontiers in Neural Circuits, 2023)
Introduction: On Earth, self-produced somatosensory stimuli are typically perceived as less intense than externally generated stimuli of the same intensity, a phenomenon referred to as somatosensory attenuation (SA). Although this phenomenon arises from the integration of multisensory signals, including vestibular signals, the specific contribution of the vestibular system and the sense of gravity to somatosensory cognition underlying distinction between self-generated and externally generated sensations remains largely unknown. Here, investigated weather temporary modulation of the gravitational input by head-down tilt bed rest (HDBR) - a well-known Earth-based analog of microgravity – might significantly affect somatosensory perception of self- and externally generated stimuli Methods: In this study, 40 healthy participants were tested using short-term HDBR. Participants received a total of 40 non-painful self- and others generated electrical stimuli (20 self- and 20 other-generated stimuli) in an upright and HDBR position while blindfolded. After each stimulus, they were asked to rate the perceived intensity of the stimulation on a Likert scale. Results: Somatosensory stimulations were perceived as significantly less intense during HDBR compared to upright position, regardless of the agent administering the stimulus. In addition, the magnitude of SA in upright position was negatively correlated with the participants’ somatosensory threshold. Based on the direction of SA in the upright position, participants were divided in two subgroups. In the subgroup experiencing SA, the intensity rating of stimulations generated by others decreased significantly during HDBR, leading to the disappearance of the phenomenon of SA. In the second subgroup, on the other hand, reversed SA was not affected by HDBR. Conclusions: Modulation of the gravitational input by HDBR produced underestimation of somatosensory stimuli. Furthermore, in participants experiencing SA, the reduction of vestibular inputs by HDBR led to the disappearance of the SA phenomenon. These findings provide new insights into the role of the gravitational input in somatosensory perception and have important implications for astronauts who are exposed to weightlessness during space missions.